Early hepatoid adenocarcinoma of the stomach with signet ring cell carcinoma: A case report and clinicopathological features - Wu, Xinglong; Di, Lianjun; Li, Chengfang; Zhang, Suyuan; Tan, Na; Huang, Jiajia; Tuo, Biguang (Frontiers in Oncology, 2023)
Background: Hepatoid adenocarcinoma of the stomach (HAS) is a rare subtype of gastric cancer with poor prognosis, and its clinicopathological features are not well understood, so the pathology from clinical biopsy is easily misdiagnosed, especially for special or atypical HAS. We present an extremely rare early HAS with signet ring cell carcinoma and evaluate its clinicopathological features. Case presentation: A 51-year-old female patient of Chinese Han ethnic with upper abdominal pain for 5 years and worsened abdominal pain for 1 month was admitted to our hospital. Esophagogastroduodenoscopy showed submucosal tumor-like elevated lesion with central depression in the greater curvature of the junction between the antrum and body. The histopathological examination from biopsy revealed medium-low differentiation adenocarcinoma with signet ring cell carcinoma. Radical gastrectomy was performed and the final diagnosis was early HAS with signet ring cell carcinoma. Conclusions: HAS with signet ring cell carcinoma is a special type of HAS and extremely rare. It is first presented for this extremely rare type of HAS, which contributes to strengthen the understanding for the clinicopathological characteristics of HAS and especially promote early detection of HAS.